Budget Management Analysis in Khyber Pakhtunkhwa for Improved Service Delivery - World Bank (World Bank, Washington, DC, 2018)
The role of public financial management (PFM) as a contributory factor in improving service delivery and stimulating economic progress is getting greater attention in the sector-related literature. A robust PFM can provide an enabling environment for improving service delivery and promoting economic growth. This report acknowledges that PFM and other factors influence the quality of service delivery. It also makes a case for how in the existing dispensation in the Khyber Pakhtunkhwa (KP) province, enhanced budget management can contribute to infrastructure development and improved service delivery. Inherent deficiencies in budget utilization in KP imply that high-budget execution needs to be looked at in combination with the quality of budget formulation in order to make the budget contributions to service delivery more meaningful.